Analisis Kesalahan Siswa Smp Kelas Vii Dalam Menyelesaikan Soal Pada Materi Himpunan - Adilistiyo, Ma'ruf Egie, Drs. Slamet H.W., M.Pd (2017)
Error in resolving the question by students can be a clue to find the factors that cause low value of learning. The discovery of these factors can be used to minimize the mistakes by students in solving math problems. This esearch aims to understand the type of error and the factors that cause students in resolving the question of content set. The type of this research is qualitative research based on his approach. The subject of this study is six students grade VII of Nusawungu 1 Junior High School. There are two udents who make mistakes of understanding, two students who make mistakes in completion process, and two students who makes mistakes in withdrawal the conclusion. The method of lecting data is tests, interviews, and documentation. The method of analyzing data performed through the reduction of the data, the presentation of data, and the withdrawal of the clusion. The validity of the data used triangulation techniques and sources. The results showed that the errors experienced by students in solving sets problem : (1) errors of erstanding; (2) error process of completion; (3) withdrawal ronclusion. Cause of error factors include a lack of understanding of students in thinking and understanding the matter of set material, lack of accuracy in completing the operation steps, the count workmanship which doesn't systematic, less train ourself to do math problem, not accustomed to write the conclusion, weak ability of students in interpreting the solution into the real context. Keywords: sets, errors, resolve the problem students